Analisis trend hujan di bandaraya Ipoh Perak 1970-2007 - Hashim Mohmadisa, Ismail Wan Ruslan, Nayan Nasir, Che Ngah Mohamad Suhaily Yusri, Ibrahim Mohd Hairy (N/A, 2012)
Analisis trend hujan di bandaraya Ipoh Perak 1970-2007 by Hashim Mohmadisa, Ismail Wan Ruslan, Nayan Nasir, Che Ngah Mohamad Suhaily Yusri, Ibrahim Mohd Hairy,